Innovative features and functionalities of an artificial pancreas system: What do youth and parents want?. Issue 10 (20th January 2021) - Commissariat, Persis V.; Volkening, Lisa K.; Butler, Deborah A.; Dassau, Eyal; Weinzimer, Stuart A.; Laffel, Lori M.
Abstract: Aims: Participant‐driven solutions may help youth and families better engage and maintain use of diabetes technologies. We explored innovative features and functionalities of an ideal artificial pancreas (AP) system suggested by youth with type 1 diabetes and parents. Methods: Semi‐structured interviews were conducted with 39 youth, ages 10–25 years, and 44 parents. Interviews were recorded, transcribed and coded using thematic analysis. Results: Youth (72% female, 82% non‐Hispanic white) were (M ± SD) ages 17.0 ± 4.7 years, with diabetes for 9.4 ± 4.9 years, and HbA1c of 68 ± 11 mmol/mol (8.4 ± 1.1%); 79% were pump‐treated and 82% were continuous glucose monitor users. Of parents, 91% were mothers and 86% were non‐Hispanic white, with a child 10.6 ± 4.5 years old. Youth and parents suggested a variety of innovative features and functionalities for an ideal AP system related to (1) enhancing the appeal of user interface, (2) increasing automation of new glucose management functionalities, and (3) innovative and commercial add‐ons for greater convenience. Youth and parents offered many similar suggestions, including integration of ketone testing, voice activation, and location‐tracking into the system. Youth seemed more driven by increasing convenience and normalcy while parents expressed more concerns with safety. Conclusions: Youth and parents expressed creative solutions for an ideal AP system to increase ease of use, enhance normalcy, and reduce burden of management. Designers of AP systems will likely benefit from incorporating the desired preferences by end users to optimize acceptance and usability by young persons with diabetes.